ACSS2 enables melanoma cell survival and tumor metastasis by negatively regulating the Hippo pathway - Zhang, Baolu; Zhu, Qing; Qu, Di; Zhao, Mao; Du, Juan; Zhang, Hengxiang; Wang, Hao; Jiang, Linhan; Yi, Xiuli; Guo, Sen; Wang, Huina; Yang, Yuqi; et al. (Frontiers in Molecular Biosciences, 2024)
Introduction: Acetyl-CoA synthetase 2 (ACSS2), one of the enzymes that catalyze the conversion of acetate to acetyl-CoA, has been proved to be an oncogene in various cancers. However, the function of ACSS2 is still largely a black box in melanoma. Methods: The ACSS2 expression was detected in melanoma cells and melanocytes at both protein and mRNA levels. Cell viability, apoptosis, migration and invasion were investigated after ACSS2 knockdown. RNA sequencing (RNA-Seq) technology was employed to identify differentially expressed genes caused by ACSS2 knockdown, which were then verified by immunoblotting analysis. Animal experiments were further performed to investigate the influence of ACSS2 on tumor growth and metastasis in vivo. Results: Firstly, we found that ACSS2 is upregulated in most melanoma cell lines compared with melanocytes. In addition, ACSS2 knockdown dramatically suppressed melanoma cell migration and invasion, whereas promoted cell apoptosis in response to endoplasmic reticulum (ER) stress. Furthermore, tumor growth and metastasis were dramatically suppressed by ACSS2 knockdown in vivo. RNA-Seq suggested that the Hippo pathway was activated by ACSS2 knockdown, which was forwardly confirmed by western blotting and rescue experiments. Taken together, we demonstrated that ACSS2 enables melanoma cell survival and tumor metastasis via the regulation of the Hippo pathway. Discussion: In summary, this study demonstrated that ACSS2 may promote the growth and metastasis of melanoma by negatively regulating the Hippo pathway. Targeting ACSS2 may be a promising target for melanoma treatment.